(untitled) (Journal of Educational Sciences, 2024)
In today’s global world, the ability to communicate effectively between people of different cultures has become very vital. As classes become more diverse, educators are faced with the challenge of preparing students for intercultural interactions and a deeper understanding of other cultures. The article explores the potential of webquest technology as a pedagogical tool for improving students’ intercultural communicative competence. Webquests are inquiry-based learning activities that use Internet resources to engage students in collaborative problem solving. The article discusses how webquests can be designed and implemented to develop students’ intercultural understanding and competence. The article presents a theoretical framework for integrating concepts and practical activities of intercultural communication in the form of webquests, offering teachers practical strategies for developing culturally diverse and relevant tasks. The article highlights the benefits of using webquests to develop intercultural communication competence, such as developing critical thinking, cooperation and empathy. The use of WebQuests also helps address potential challenges in effectively incorporating intercultural components into WebQuests, ensuring that students gain meaningful intercultural experiences. Explores how students can develop cultural awareness, empathy, and effective communication skills by using diverse perspectives, cultural artifacts, and virtual interactions. 103 Miras University students took part in the empirical part of the study. The results indicate that WebQuests provide a valuable platform for students to explore, analyze, and interact with different cultures, promoting a deeper understanding and appreciation of diversity. The article concludes by discussing implications for educational practice and providing recommendations for teachers to effectively integrate WebQuests into their curriculum to enhance students’ intercultural communicative competence. Keywords: WebQuest, intercultural, communicative, competence, students, education.